Iowa RBA, March 30, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for March 30, 1998. Highlights include Ferruginous Hawk, Glaucous Gull and Eurasian Collared Dove. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed